Family empowerment strategy and stunting prevention through moringa tree planting movement - Rahmah, Nur; Alam, Syamsul; Arranury, Zilfadhilah; Kahfi, Muhammad; Aswadi, Aswadi; Syarfaini, Syarfaini (Sociality: Journal of Public Health Service, 2025)
Stunting is a significant global health problem, with an estimated 149 million children under five experiencing this condition in 2018. Moringa is a nutrient-rich plant recommended by WHO as an alternative food to overcome nutritional problems or malnutrition. This service aims to increase knowledge about the use of moringa to prevent stunting, encourage active community participation in planting moringa trees in every home, and hone family skills in innovation in processing moringa-based food. The service method uses a Participatory Action Research (PAR) approach. This program is conducted through education, training, and mentoring using lecture, discussion, and direct practice methods. The results of the service showed a positive response from the community, as seen from their activeness during education and socialization of Moringa-based food innovations. This education succeeded in increasing public understanding about using Moringa leaves to prevent stunting, with pre-test and post-test data showing an increase in knowledge from 44.60 to 93.00. This program also distributed 500 Moringa tree seeds and trained people to make processed Moringa products into innovative foods, such as pudding and brownies, opening up economic opportunities. This program is expected to provide sustainable benefits for the health and welfare of the local economy.